Personal Branding Prilly Latuconsina di Media Sosial Instagram (Analisis Isi Kualitatif Konten Akun Instagram @Prillylatuconsina96) - Ashari, Anita; Ainun Ni’matu Rohmah; Silviana Purwanti; Kheyene Molekandella Boer (Journal of Management and Bussines (JOMB), 2026)
This study aims to analyze Prilly Latuconsina's personal branding on Instagram through the account @prillylatuconsina96 based on the concept of The Eight Laws of Personal Branding and from the perspective of agenda-setting theory. The research method used was a qualitative approach with descriptive research through qualitative content analysis of Instagram reels content for the period April 2024, selected using purposive sampling, involving three coders competent in the field of communications. The results indicate that the personal branding developed is strong and effective, characterized by high achievements in the indicators of personality, appearance, unity, and reputation, which obtained maximum scores, as well as indicators of specialization, leadership, and diversity, which were in the good category, thus reflecting a multitalented, inspiring, and influential person. However, in the indicator of constancy, inconsistencies were found in character presentation, resulting in the lack of development of a strong distinctive characteristic. The conclusion of this study is that the personal branding displayed is able to build a positive, authentic, and influential image in accordance with the principles of agenda-setting, although increased consistency is still needed to strengthen self-identity in the public eye.   Keywords: Personal Branding, Instagram, Influencer, Agenda Setting